Pengaruh Rasa Bersyukur Terhadap Kebahagiaan Pada Dewasa Muda - Rizka Dinanti; Wustari L. Mangundjaya (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study discusses about effect of gratitude to happiness in psychology students at X University who are young adults. The purpose of this study is the research want to develop this study about effect of gratitude to happiness in positive psychology study. This study used quantitative method with simple linier regression analysis. The respondents of this study were 108 psychology students aof X University.  Respondent was chosen using convenience sampling and  data was collected by online through google form. The results of this study indicates that psychology students have a high sense of gratitude and happiness. Moreover, the results showed that  gratitude had a high  effect on happiness of the students who categorized at young adults of the faculty of Psychohology of  X University.  From the results, it also showed that in order to develop a sense of happiness then lots of activies such as workshop, training, coaching and many other activities needs to be done to develop a sense of grartitude in university students.